KINERJA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DALAM PEMBANGUNAN DRAINASE DI KOTA DUMAI TAHUN 2020 - Pratama, Rafika; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Drainage has become one of the most important urban infrastructure. The quality of management of a city is reflected in the quality of drainage in that city. The Office of Public Works and Spatial Planning is a government agency that is responsible for the management, development and maintenance of drainage in a city. The problem in this study is the slow construction of drainage by the Municipal Government of Dumai, as well as flooding in community areas. It is known that the construction of drainage to minimize existing flooding. This study aims to describe the performance of the Department of Public Works and Planning of the City of Dumai in constructing drainage. This study uses performance appraisal indicators consisting of productivity, service quality, responsiveness, responsibility and accountability. This type of research is descriptive qualitative in nature to describe and explain the performance of the Public Works and Spatial Planning Office in the construction of drainage in the City of Dumai. The subject of this research is the Public Works and Spatial Planning Office which is responsible for Cipta Karya. Data collection methods used in this study were interviews and documentation. Data analysis was carried out by analyzing qualitative data by summarizing, categorizing and drawing conclusions. The results of this study indicate that the performance of the Department of Public Works and Spatial Planning in the construction of drainage in Dumai City cannot be said to be good, the drainage that is built cannot function properly resulting in inundation and flooding, the drainage that is built does not meet existing standards, there is no it is clear where the direction of the existing channels and normalization of drainage must be carried out routinely. Keywords: Performance productivity, performance service quality, performance responsiveness